2006
DOI: 10.2486/indhealth.44.604
|View full text |Cite
|
Sign up to set email alerts
|

A Field Evaluation Method for Assessing Whole Body Biomechanical Joint Stress in Manual Lifting Tasks

Abstract: Work-related musculoskeletal injuries are often associated with overexertion of the body at work. The manual materials handling activity of lifting is a major source of work-related musculoskeletal disorders. Biomechanical evaluation offers useful information about the physical stress imposed on the worker's body joints; however, biomechanical analysis is usually tedious and complex. For evaluation purpose, the biomechanical method needs to be easy to apply in a field environment. Manual lifting occurs as one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Numerous other data sets contain 5 and 95 % tile for a broad range of humans (Opeshaw and Taylor 2006). Lin et al (2006) reported that manual material handling (MMH) especially lifting represents a major occupational safety and health risk in places such as industries and hospitals. Musculoskeletal and low-back disorders are often attributed to over exertion of the body when the operator works to meet the demand of MMH tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous other data sets contain 5 and 95 % tile for a broad range of humans (Opeshaw and Taylor 2006). Lin et al (2006) reported that manual material handling (MMH) especially lifting represents a major occupational safety and health risk in places such as industries and hospitals. Musculoskeletal and low-back disorders are often attributed to over exertion of the body when the operator works to meet the demand of MMH tasks.…”
Section: Introductionmentioning
confidence: 99%
“…1) lifting, elbow flexion, wrist extension, and ulnar deviation are clinically relevant. The following average ranges of motion were recorded for each joint: 50° for arm lifting (5° difference between the conditions), 56° for elbows (6° difference between the conditions), 38° for wrist extension (4° difference between the conditions), and 31° for ulnar deviation of the wrist (3° difference between the conditions).…”
Section: Fs-g Fs-gt Fs-amentioning
confidence: 99%
“…This activity is considered to cause most of the health-related costs and problems in work environments 1 .…”
Section: Introductionmentioning
confidence: 99%
“…A second and not negligible aspect is the exposure of single health care, that is calculated on the basis of a "presumed" patients handling, and not on the direct observation of quality and quantity of handling operations (impossible thing). The advanced hypothesis implies that in all situations, where not self-sufficient patients are present, all health workers perform a substantially homogeneous activity, with a minimum number of lifts-shifts, as for example the personal hygiene operations (36)(37)(38)(39)(40)(41).…”
Section: More Exposed Men Less Exposed Men More Exposed Women Less Exmentioning
confidence: 99%